2018
DOI: 10.1155/2018/7846350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Locally Manufactured Niger Seed Oil on Lipid Profile Compared to Imported Palm and Sunflower Oils on Rat Models

Abstract: Background Different types of dietary lipids have been shown to affect lipid metabolism and lipid profile differently. Objective This study aims to assess the effect of local niger seed oil on serum lipid profile compared to palm oil and sunflower oil in rats. Methods The effect of the 15% plant oils on serum lipid profile, body weight gain percentage, and feed efficiency ratio was assessed after 8 weeks of experimental period. Results and Conclusion The 15% niger seed oil showed decrease and increase in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Mean cardiac total cholesterol and total triglyceride of rats fed with E. pursaetha seed oil were higher than those fed with groundnut oil and normal rat diet. This is in line with the report of Mekonnen et al [24] that the levels of total cholesterol, HDL-c, LDL-c and TAG were significantly (p<0.05) higher in rats fed with 15 % palm oil compared to control groups.…”
Section: Cardiac and Plasma Lipidssupporting
confidence: 93%
“…Mean cardiac total cholesterol and total triglyceride of rats fed with E. pursaetha seed oil were higher than those fed with groundnut oil and normal rat diet. This is in line with the report of Mekonnen et al [24] that the levels of total cholesterol, HDL-c, LDL-c and TAG were significantly (p<0.05) higher in rats fed with 15 % palm oil compared to control groups.…”
Section: Cardiac and Plasma Lipidssupporting
confidence: 93%
“…A previous study has demonstrated that grape seed oil and corn oil, that were rich in linoleic acid or omega-6 fatty acids, tended to decrease serum cholesterol levels in rats [70]. Similarly, linoleic acid-rich niger seed oil was found to display a hypolipidemic effect through the facilitation of lipid transportation and metabolism, possibly lowering the risk of cardiovascular disease development [71]. Consistently, a combination diet of proteins, perilla seed oil, linoleic acid and α-linolenic acid (per oral) was found to decrease plasma triglyceride and cholesterol levels in rats [72].…”
Section: Discussionmentioning
confidence: 97%
“…The mixtures were left to absorb the fried oils at room temperature overnight before the feeding was conducted. 28 , 29 …”
Section: Methodsmentioning
confidence: 99%